Response of Guiana dolphins to the construction of a bridge in Ilhéus, Northeastern Brazil. - Yvonnick Le Pendu; Alice Lima; Erica Gomes; Winnie Silva; Khamila Tondinelli Souza Cruz; Gastón Andrés Fernandez Giné (PLoS ONE, 2024)
This study aimed to investigate whether the use of space and movements of Guiana dolphins were altered during the construction of a cable-stayed bridge at the mouth of the Cachoeira River estuary in Ilhéus, Brazil. We described and compared the visitation rate, use of space, and movements of the Guiana dolphins across two periods: before the construction began (2015-2016) and during the construction of the bridge (2017-2020). A theodolite and a total station were used to observe and record the trajectories of the dolphins. From these trajectories, we estimated the Utilization Distribution (UD) using the biased random bridge kernel (BRBK) method, the area of use, and the core area, based on the 95% and 50% BRBK density, respectively. The dolphins did not change their visitation frequency to the estuary. No significant change in area fidelity was identified by comparing the overlap of areas used during two-month periods. No change occurred in the velocity and linearity of the trajectories of the dolphins swimming close to the bridge. However, contrary to expectations, the results indicated an increase in the use of areas close to the bridge during its construction. This may have been caused by the change in the distribution of their prey in the estuary due to the emergence of a sandbank near the bridge. Bridge construction work seems not to have directly affected the Guiana dolphins' use of the area, but the impact of the construction on the local topography has changed their areas of use and core areas of activity.